1998
DOI: 10.1046/j.1365-2265.1998.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Lean body mass as a determinant of thyroid size

Abstract: In healthy adults, lean body mass rather than body weight explains the differences in thyroid volume between males and females and between obese and non-obese subjects. Lean body mass appears to be a major determinant of thyroid size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
3
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 13 publications
4
45
3
4
Order By: Relevance
“…This difference was related to the amount of lean body mass rather than to body weight by itself (59). After weight loss, a reduction in thyroid volume was also observed (60).…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 92%
See 1 more Smart Citation
“…This difference was related to the amount of lean body mass rather than to body weight by itself (59). After weight loss, a reduction in thyroid volume was also observed (60).…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 92%
“…Data regarding the circulating concentrations of thyroid hormones are less univocal because the serum levels of FT 3 were reported as increased, unchanged, or decreased. On the other hand, most studies reported a general trend toward low/normal levels of FT 4 in obese subjects (59,60,61,62,63,64,65,66). Lately, the relation between adiposity and serum TSH, FT 3 , and FT 4 was evaluated in a large, representative sample of the adult population from the National Health and Nutrition Examination Survey 2007-2008 (67).…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 99%
“…How these affect thyroid volume is unclear, but thyroid volume for BSA can be expected to differ between populations. A recent report has suggested that, in adults, thyroid size is determined largely by lean body mass (22). Whether this is also true in growing children remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from our group questioned whether an elevated serum TSH alone provides sufficient evidence for a diagnosis of subclinical hypothyroidism in patients with morbid obesity (19). Little has been reported on the morphology of the thyroid gland in adults with morbid obesity (20,21). A recent study, performed in obese children, showed for the first time that obesity is associated with structural changes in thyroid morphology, as assessed by US, which are unrelated to thyroid autoimmunity (22).…”
Section: Introductionmentioning
confidence: 99%